“Children of War”: Difficulties of Socialization and Peculiarities of Perception of the World - A.G. Samokhvalova; O.N. Vishnevskaya; E.V. Tikhomirova; N. Shipova (Социальная психология и общество)
Objective. Identification of the difficulties of socialization and peculiarities of perception of the world in the conditions of a hybrid war among adolescents living in a zone of military conflict and in territories remote from military operations. Background. The child's psyche is most susceptible to trauma in conditions of military conflict. The sociocultural context of a hybrid war, combining military and non-military methods of destructive influence on the individual, puts the process of socialization of the younger generation at risk. It is extremely important in modern conditions to identify the difficulties of socialization and the specificity of the image of the world among “children of war”. Study design. The study tested the hypothesis about the presence of general difficulties in socialization among “children of war” living in the epicenters of military operations and in remote areas; and also using the Mann-Whitney test, differences were determined in reactions to traumatic stress, in the manifestation of communication difficulties and aggressiveness, in the subjective-emotional attitude to the world in adolescents of the two groups. Participants. The sample included 94 respondents aged 15 to 17 years (M = 16,1; SD = 2,65) and consisted of two groups: teenagers living from the beginning of the special military operation to the present time in the Lugansk People's Republic (N = 47), as well as Kostroma teenagers (N = 47). Measurements. The methodological design included the “Children's Scale for Diagnosing the Severity of Traumatic Stress Reactions” (CPTS-RI Scale), R. Pinos, A. Steinberg, adapted by E.S. Molchanova; questionnaire “Difficulties in communicating with peers and adults” A.G. Samokhvalova; projective test “Hands” (hand-test) by E. Wagner, adapted by T.N. Kurbatova; technique “The world I live in... What is it like?” M.A. Odintsova. Results. General barriers to socialization characteristic of “children of war” have been identified – the presence of basic and meaningful difficulties that arise in communicating with peers and adults, aggressive tendencies of social interaction. Differences have also been established: Lugansk teenagers are characterized by a tendency to get closer to adults, high self-control in communication, fear of using new methods of communication, meaningfulness of the world and a willingness to change it; for Kostroma teenagers – a tendency to separate from adults, verbal and non-verbal difficulties, unwillingness to admit their mistakes, demonstrativeness, an emotionally positive attitude towards the world without deep understanding of it. Conclusions. The sociocultural context of a hybrid war creates a special, traumatic developmental situation for a teenager, causing difficulties in communication and social interaction, forming a specific image of a “dangerous world”.